Technology and Demand Drivers of Productivity Dynamics in Developed and Emerging Market Economies - Dieppe, Alistair; Francis, Neville; Kindberg-Hanlon, Gene (World Bank, Washington, DC, 2021)
Frequently, factors other than structural developments in technology and production efficiency drive changes in labor productivity in advanced and emerging market and developing economies (EMDEs). This paper uses a new method to extract technology shocks that excludes these influences, resulting in lasting improvements in labor productivity. The same methodology in turn is used to identify a stylized example of the effects of a demand shock on productivity. Technology innovations are accompanied by higher and more rapidly increasing rates of investment in EMDEs relative to advanced economies, suggesting that positive technological developments are often capital-embodied in the former economies. Employment falls in both advanced economies and EMDEs following positive technology developments, with the effect smaller but more persistent in EMDEs. Uncorrelated technological developments across economies suggest that global synchronization of labor productivity growth is due to cyclical (demand) influences. Demand drivers of labor productivity are found to have highly persistent effects in EMDEs and some advanced economies. Unlike technology shocks, however, demand shocks influence labor productivity only through the capital deepening channel, particularly in economies with low capacity for counter-cyclical fiscal policy. Overall, non-technological factors accounted for most of the fall in labor productivity growth during 2007-08 and around one-third of the longer-term productivity decline after the global financial crisis.